Effect Of Estimated Waiting-Time Provision On Patients' Satisfaction With Emergency Department: A Randomized Controlled Trial - Khalid Nabeel Almulhim; Lina Abdulaziz AlMudayris; Zeyad Khalid Alshehri; Ahmed Khalid Alnawah; Danah Abdulaziz Aljeri; Abdulaziz Shary Hadadi (Saudi Journal of Emergency Medicine)
Background: Patient satisfaction is a quality measure that may provide important details about the medical care given by providers. A higher patient compliance rates and fewer malpractice claims are associated with patient satisfaction. Evaluating patient experience and satisfaction of emergency beneficiaries have been conducted through various hospitals across the Gulf region, and yet no comparable study has been done in King Fahad Hospital. Therefore, our study aimed to examine the effect of estimated time provision on patient satisfaction with emergency care in KFHH. Method: A randomized controlled trial was conducted from 1st to 30th of November 2023 at King Fahad Hospital Emergency department in Al-Hofuf. It included those triaged as 3 and above and those 18 and above. Patients were divided into two groups, an intervention group was provided the time, and 2 questionnaires were used at both triage entrance and after being seen by the physician. Result: A total of 190 patients satisfied the inclusion criteria were included in the analysis, and the majority (62.1%) were located in triage entrance, while 37.9% were inside the ED rooms. Mann-Whitney U test was used to obtain the p-value and showed no difference in the level of satisfaction between patients who were provided with the estimated waiting time and those who were not (0.962). Conclusion: This study demonstrates the importance of timely care delivery, and the findings highlight the complex nature of patient satisfaction, indicating that factors beyond wait times also play a pivotal role in shaping patients' perceptions of their ED experience. [SJEMed 2024; 5(1.100): S65-S65]